Tailoring management response to negative reviews: The effectiveness of accommodative versus defensive responses. (July 2018) - Li, Chunyu; Cui, Geng; Peng, Ling
Abstract: Firms increasingly respond to online customer reviews on public platforms to influence prospective consumers and enhance profitability. This paper highlighted the importance of semantically tailoring management responses according to the content of the reviews and examined the impact of such responses on prospective consumers and future sales. Based on a field study and an experiment, we found that an accommodative response to the product failure review and a defensive response to the ordinary negative review were effective at increasing sales and enhancing consumer purchase intentions. The effect of management response was mediated by the reduced causal attribution of negative reviews to firms. Our findings furnish meaningful implications for firm interventions on online platforms. Highlights: Firms should semantically tailor management response according to review content. Accommodative response is effective for product failure reviews. Defensive response is effective for ordinary negative reviews. The reduced attribution of negative review towards firms mediates the effect. Neither response to positive review nor untailored response is effective.